Evaluation of the Antitumor and Antiproliferative Potential of Synthetic Peptides Derived from IsCT1, Associated with Cisplatin, in Squamous Cell Carcinoma of the Oral Cavity - Laertty Garcia de Sousa Cabral; Cyntia Silva de Oliveira; Vani Xavier Oliveira; Ellen Paim de Abreu Paulo; Jean-Luc Poyet; Durvanei Augusto Maria (Molecules, 2025)
Head and neck squamous cell carcinoma (SCC), particularly in the oral cavity, is among the most prevalent and lethal forms of cancer globally. Current therapeutic strategies, predominantly involving cisplatin, face challenges like chemoresistance and toxicity to normal cells, justifying the exploration of new approaches. This study evaluates the antitumor, antiproliferative, and immunomodulatory potential of a synthetic peptide derived from IsCT1 (Isalo scorpion cytotoxic peptide), named AC-AFPK-IsCT1, in combination with cisplatin in oral squamous cell carcinoma cellular models. Tumor and normal cells were treated with varying concentrations of cisplatin and peptide, and the cytotoxicity was measured through an MTT assay, while apoptosis and cell cycle alterations were assessed via flow cytometry. Interestingly, the combination of AC-AFPK-IsCT1 with cisplatin exhibited higher specificity for tumor cells, significantly reducing IC50 values compared to cisplatin used as a single agent. Moreover, the combination treatment induced pronounced S-phase cell cycle arrest and enhanced apoptotic activity, evidenced by the upregulation of caspase-3, caspase-8, and p53, while maintaining low toxicity in normal fibroblast cells. The peptide also modulated the mitochondrial membrane potential, further contributing to the activation of intrinsic apoptotic pathways. The data suggest that AC-AFPK-IsCT1 potentiates the antitumor effects of cisplatin by engaging both intrinsic and extrinsic apoptotic pathways while preserving normal cell viability. These findings underscore the potential of combining cisplatin with AC-AFPK-IsCT1 as a promising therapeutic strategy for improving the efficacy of chemotherapy in SCC, reducing systemic toxicity, and overcoming chemoresistance.